The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.phrs.2017.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Renin angiotensin aldosterone inhibition in the treatment of cardiovascular disease

Abstract: A collective century of discoveries establishes the importance of the renin angiotensin aldosterone system in maintaining blood pressure, fluid volume and electrolyte homeostasis via autocrine, paracrine and endocrine signaling. While research continues to yield new functions of angiotensin II and angiotensin-(1-7), the gap between basic research and clinical application of these new findings is widening. As data accumulates on the efficacy of angiotensin converting enzyme inhibitors and angiotensin II recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
91
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(96 citation statements)
references
References 267 publications
0
91
0
5
Order By: Relevance
“…It should be noted that previous reports of blood pressuring lowering with AGT inhibition using RNA-based approaches have been described 24,25 ; however, these studies have an important limitation because of their use of SHRs, a model that already displays robust antihypertensive responses to standard RAAS blockade. In addition, the early ASO studies reported only 40% to 50% maximal reductions of plasma AGT, 26 which would not have been predicted to elicit maximal BP reductions. Thus, the studies described herein are the first demonstration of the pharmacology of Plasma AGT levels are close to the Michaelis-Menten constant (K m ) of renin; thus, plasma Ang I formation is dependent on both AGT and renin.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that previous reports of blood pressuring lowering with AGT inhibition using RNA-based approaches have been described 24,25 ; however, these studies have an important limitation because of their use of SHRs, a model that already displays robust antihypertensive responses to standard RAAS blockade. In addition, the early ASO studies reported only 40% to 50% maximal reductions of plasma AGT, 26 which would not have been predicted to elicit maximal BP reductions. Thus, the studies described herein are the first demonstration of the pharmacology of Plasma AGT levels are close to the Michaelis-Menten constant (K m ) of renin; thus, plasma Ang I formation is dependent on both AGT and renin.…”
Section: Discussionmentioning
confidence: 99%
“…RAAS activation is involved in the development of heart failure and is one of the main factors contributing to ventricular remodeling. Effective blockade of the RAAS is important for improving heart failure and ventricular remodeling in heart failure . Evidence has indicated the reciprocal interaction between LOX and RAAS in cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, CHF is characterized by overactivation of the renin‐angiotensin‐aldosterone system (RAAS), which plays an important role in the development of heart failure . Evidence indicates that the blockade of the RAAS is effective for the treatment for heart failure …”
Section: Introductionmentioning
confidence: 99%
“…Thus, two of the major advances in clinical medicine over the last 50 years can be traced back to the work described in Vane's Gaddum Lecture. It is worth noting that both lowdose aspirin (Bibbins-Domingo, 2016;Iacono et al, 2019;Seidu et al, 2019) and the RAS inhibitors (Ferrario & Mullick, 2017;Esser & Zraika, 2019;. Stolfo & Savarese, 2019) are still providing clinical benefit to many millions of patients worldwide.…”
Section: Discussionmentioning
confidence: 99%